Biocompatible and stable magnetosome minerals coated with poly-l-lysine, citric acid, oleic acid, and carboxy-methyl-dextran for application in the magnetic hyperthermia treatment of tumors. Issue 36 (8th September 2017) - Mandawala, Chalani; Chebbi, Imène; Durand-Dubief, Mickael; Le Fèvre, Raphael; Hamdous, Yasmina; Guyot, François; Alphandéry, Edouard
Abstract : Magnetic hyperthermia in which magnetic nanoparticles are introduced into tumors and exposed to an alternating magnetic field, appears to be promising. Abstract : Magnetic hyperthermia, in which magnetic nanoparticles are introduced into tumors and exposed to an alternating magnetic field (AMF), appears to be promising since it can lead to increased life expectancy in patients. Its efficacy can be further improved by using biocompatible iron oxide magnetosome minerals with better crystallinity and magnetic properties compared with chemically synthesized nanoparticles (IONP – Iron Oxide Nanoparticles). To fabricate such minerals, magnetosomes are first isolated from MSR-1 magnetotactic bacteria, purified to remove potentially toxic organic bacterial residues and stabilized with poly-l -lysine (N-PLL), citric acid (N-CA), oleic acid (N-OA), or carboxy-methyl-dextran (N-CMD). The different coated nanoparticles appear to be composed of a cubo-octahedral mineral core surrounded by a coating of different thickness, composition, and charge, and to be organized in chains of various lengths. The in vitro anti-tumor and heating efficacies of these nanoparticles were examined by bringing them into contact with GL-261 glioblastoma cells and by applying an AMF. This led to a specific absorption rate of 89–196 W gFe −1, measured using an AMF of 198 kHz and 34–47 mT, and to percentages of tumor cell destruction due to the exposure of the nanoparticles to the AMF of 10 ± 3% to 43 ± 3% depending on the coating agent. These results show the potential of this protocol for the tumor treatment by magnetic hyperthermia.